2004
DOI: 10.1111/j.1523-1755.2004.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP, at the hub of the cystic cycle

Abstract: EDITORIALCyclic AMP, at the hub of the cystic cycle Half a century after its discovery, new roles for adenosine 3 ,5 -cyclic monophosphate (cAMP) continue to be discovered. The article by Belibi et al [1] in this issue of Kidney International, implicates cAMP in the pathogenesis of autosomal-dominant and recessive polycystic kidney diseases (ADPKD and ARPKD) and provides a target for the pharmacologic treatment of these disorders.Cyclic AMP is a ubiquitous and versatile second messenger. Extracellular ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 17 publications
2
42
0
1
Order By: Relevance
“…Second, relatively high levels of forskolin-like activity were discovered in the cyst fluid of a 2-wk-old infant with ARPKD. cAMP is a major growth factor in PKD progression through its effects to stimulate fluid secretion into the cysts and its mitogenic effect on mural epithelial cells (23). Recent studies of hereditary polycystic disease in rodents showed that suppres- Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Second, relatively high levels of forskolin-like activity were discovered in the cyst fluid of a 2-wk-old infant with ARPKD. cAMP is a major growth factor in PKD progression through its effects to stimulate fluid secretion into the cysts and its mitogenic effect on mural epithelial cells (23). Recent studies of hereditary polycystic disease in rodents showed that suppres- Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective, randomized, crossover, double-blind, placebo-controlled study showed that 6 months of octreotide therapy limited kidney volume growth versus placebo in 12 patients with ADPKD (6) possibly through inhibition of cAMP production and activity (7). To assess the treatment effect on polycystic liver, in this post hoc analysis of the above study we primarily compared liver volume changes during octreotide and placebo therapy in the same population.…”
mentioning
confidence: 99%
“…Increased intracellular cAMP is a common feature of both ARPKD and ADPKD renal cells 22 (Figure). Renal cAMP concentrations are increased in the pck rat (a model in which the rat orthologue of PKHD1 is disrupted), as well as the pcy muse (modeling human nephronophthisis) and the Pkd2 WS25 mouse (modeling human ADPKD).…”
Section: Genetics and Cell Biology Of Arpkd/chfmentioning
confidence: 99%